TAHFIDZ AL QURAN CLASS: RELIGION COMMODIFICATION AND POPULAR CULTURE IN MUSLIM MIDDLE CLASS - Rholand Muary; Puteri Atikah (FISIP Universitas Malikussaleh, 2023)
The purpose of this study was to learn about the practice of religion commodification in the Al-Quran tahfidz program, as well as the strategies used to capture the middle-class Islamic market. The study was carried out in North Sumatra Province, specifically in Medan and the Deli Serdang. This study conducted in three schools are the Yayasan Pendidikan Shafiyyatul Amaliyah (YPSA), Rumah Tahfidz al Irsyad, and the Markaz Tahfiz Ali Syamsi. The research method used is a qualitative research method, which researchers believe is capable of exploring and describing data about the practice of religion commodification and marketing strategies in the Al-Quran tahfidz program. According to this study, a new Islamic middle class group emerged in post-New Order Indonesia. The emergence of a new Muslim middle class has resulted in a consumption pattern that differs from that of previous generations. They want to enjoy modernity while maintaining their Muslim piety. Capitalism responds well to this circumstance, resulting in the commodification of religion. Finally, the Islamic middle class's consumption pattern is currently a culture of including children in the Al-Quran tahfidz program. This culture paved the way for the establishment of Al-Quran tahfidz educational institutions. This consumption pattern is inextricably linked to the role of popular culture in the mass media in the creation of Islamic popular culture.Penelitian ini dilakukan untuk mengetahui praktek komodofikasi agama pada program tahfidz Al Quran dan strategi yang digunakan untuk merebut pasar kelompok Islam menengah. Penelitian dilakukan di Provinsi Sumatera Utara, khususnya di Kota Medan dan Kabupaten Deli Serdang. Adapun tiga fokus lokasi penelitian ini antara lain Yayasan Pendidikan Shafiyyatul Amaliyah (YPSA), Rumah Tahfidz al Irsyad, serta Markaz Tahfiz Ali Syamsi. Metode penelitian yang digunakan yaitu metode penelitian kualitatif yang dianggap peneliti bisa menggali dan mendeskripsikan data tentang praktek komodifikasi agama dan strategi pemasaran dalam program tahfidz Al Quran. Adapun hasil dari penelitian ini menunjukan bahwa muncul kelompok kelas menengah Islam baru di Indonesia pasca Orde Baru. Kemunculan kelas menengah Muslim baru ini memiliki pola konsumsi yang relative berbeda dengan generasi sebelumnya. Mereka ingin menikmati moderenitas, tapi tanpa meninggalkan kesalehannya sebagai seorang Muslim. Kondisi inilah yang direspon dengan baik oleh kapitalisme sehingga melahirkan komodifikasi agama. Kesimpulannya pola konsumsi kelas menengah Islam ini saat ini budaya mengikutsertakan anak dalam program tahfidz Al Quran. Budaya ini kemudian membuka peluang akan munculnya lembaga pendidikan tahfidz Al Quran. Pola konsumsi ini tidak lepas dari peran budaya popular di media massa yang menciptakan budaya popular Islam.